As plantas comestíveis no Brasil dos séculos XVI e XVII segundo relatos de época - Tomchinsky, Bernardo; Ming, Lin Chau (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2019)
Abstract This work aimed to study the edible flora in Brazil during the 16th and 17th centuries from analyses of texts of 18 authors who visited the country during this period. The cited plants were identified by similarity through the descriptions and images in the studied texts, area of ​​occurrence, popular name, and the analysis of other botanical studies. In all, 827 citations of food plants were found in the texts studied; it was possible to identify 183 species belonging to 61 different botanical families; 37 citations weren’t possible to identify. Of the plants identified, 55% are native to Americas, including Brazil and other american countries, 8% are endemic to Brazil, 37% are exotic to Americas and for two plants it wasn’t possible to find their origin. From this data it is possible to say that during the 16th and 17th century there was the use of a great cornucopia of plant species by the brazilian population, especially cassava, pineapple, genipap, sweet potato and corn. The presence of exotic and naturalized species native to the Americas shows the exchange of germplasm that already existed among pre-columbian populations. During the 16th and 17th century there was an intense exchange of plants with other regions of the world promoted by Europeans, which resulted in the introduction of many cultivated and exotic species that became important in the brazilian diet. Finally we can say that many of those plants used during that time are now neglected.

Resumo Este trabalho objetivou estudar a flora comestível do Brasil nos séculos XVI e XVII a partir dos textos de 18 autores que estiveram no país durante este período. As plantas citadas foram identificadas por similaridade a partir das descrições textuais e imagens disponíveis nas obras estudadas, considerando a origem, área de ocorrência e nome popular, além da análise de outros estudos botânicos. Ao todo foram levantadas 827 citações de plantas alimentícias nas obras estudadas, das quais foi possível identificar 183 espécies pertencentes a 61 famílias botânicas diferentes. De 37 espécies não foi possível chegar a nenhuma aproximação botânica. Das plantas identificadas, 55% são nativas das Américas, incluindo as do território brasileiro e de outros países americanos, 8% são endêmicas e só ocorriam no Brasil, 37% são exóticas das Américas e duas plantas não tiveram sua origem definida. A partir deste trabalho foi possível observar que havia, durante os séculos XVI e XVII, o uso de uma grande diversidade de espécies na alimentação dos brasileiros, com destaque para a mandioca, abacaxi, jenipapo, batata-doce e milho. A presença de espécies nativas das Américas, mas exóticas do Brasil, como o milho e a batata-doce, evidencia a troca de germoplasma que já existia entre populações indígenas. Nos séculos XVI e XVII ocorreu uma rápida e intensa troca de plantas com outras regiões do mundo promovida pelos europeus, que resultou na introdução de uma grande quantidade de espécies exóticas as quais acabaram ganhando grande importância na dieta dos brasileiros. Por fim, observamos que muitas das plantas citadas estão em desuso até os dias de hoje.
Edible plants used in Brazil during the 16th and 17th century according to historical reports
Keywords: historical ethnobotany; history of Brazil; germoplasm exchange; edible plants; etnobotânica histórica; história do Brasil; intercâmbio de germoplasma; plantas alimentícias